Cognitive impairment in REM-sleep behaviour disorder and individuals at risk of Parkinson's disease. (April 2023) - Nagy, A.V.; Leschziner, G.; Eriksson, S.H.; Lees, A.; Noyce, A.J.; Schrag, A.
Abstract: Background: Mild cognitive impairment (MCI) is commonly present at the time of Parkinson's Disease (PD) diagnosis, but its prevalence amongst individuals at increased risk of PD is unclear. Methods: Cognition was assessed using the Montreal Cognitive Assessment (MoCA) in 208 participants in the PREDICT-PD study, and 25 participants with REM-sleep behaviour disorder (RBD). Prevalence of MCI level I was determined in all participants, and level II MCI in the RBD sub-group. Results: Total MoCA scores were worse in the higher risk than the lower risk group defined as those below the 15th percentile of risk (p = 0.009), and in the RBD group compared to all healthy participants (p < 0.001). The prevalence of MCI level I was 12.8% in the lower-risk, 21.9% in the higher-risk (within the highest 15th percentile) and 64% in RBD participants; 66% of RBD participants had MCI level II with multi-domain MCI, but particularly attention and memory deficits. Conclusions: Cognitive impairment is increased in different groups at higher risk of PD, particularly in the subgroup formally diagnosed with RBD. Highlights: People with increased risk scores for Parkinson's disease show reduced cognitive function. There is a particularly high rate of cognitive impairment in patients with REM-sleep behaviour disorder. These are present especially in the domains of attention and memory.